Optical soliton solutions, dynamical and sensitivity analysis for fractional perturbed Gerdjikov–Ivanov equation - Muhammad Shakeel; Fehaid Salem Alshammari; Hameed Gul Ahmadzai (Scientific Reports)
Abstract This work constructs the distinct type of solitons solutions to the nonlinear Perturbed Gerdjikov-Ivanov (PGI) equation with Atangana’s derivative. It interprets its optical soliton solutions in the existence of high-order dispersion. For this purpose, a wave transformation is applied to convert the fractional PGI Equation to a non-linear ODE. Solitons solutions and further solutions of the obtained model are sorted out by using the Sardar sub-equation (SSE) method and the generalized unified method. The different types of soliton solutions such as bright, kink, periodic, and exact dark solitons are achieved. Dynamical and sensitivity analysis is carried out for the obtained results. 3D, 2D, and contour graphs of attained solutions are presented for elaboration. Nonlinear model have played an important role in optic fibber, optical communications and optical sensing.